The development of Critical Thinking Skills during Practical Training: The Perspectives of Pedagogical Supervisors and Sports and Physical Education Trainees - Nziengui Nsonde, Beralex Vianney; Mandoumou, Paulin; Kpazai, Georges (European Scientific Journal, ESJ, 2024)
In the Republic of Congo, initial teacher training has both a theoretical and a practical dimension. Theoretical training takes the form of theoretical courses within the training institution itself. Practical training, on the other hand, takes place in professional settings (secondary schools). This comparative study consisted of identifying the conceptions relating to the development of critical thinking by educational supervisors and by student-trainees. Inscribed in a qualitative methodological approach, this research was based on Eric Lavertu’s (2013) conceptual approach to the development of critical thinking in internships. Eight (08) educational supervisors and nineteen (19) student-trainees voluntarily participated in the study via three focus groups. The results obtained, following a content analysis of the corpus collected, reveal several didactic-pedagogical devices for the development of student-trainees’ critical thinking, both according to the perception of pedagogical supervisors, and also, according to that of student-trainees. As didactic-pedagogical devices, educational supervisors identify three: the communication strategies highlighted by the supervisor, the climate of exchange established by the supervisor and the attitude of the supervisor. The student-trainees, for their part, emphasize the educational supervision environment, the attitude of the supervisor and the attitude of the student-trainee. Thus, to promote the development of critical thinking among student trainees, the measures mentioned specify that the supervisor must implement a pedagogical approach to supervision anchored in a social-constructivist paradigm to support the development of the student, using a reflective approach in support. In addition, these mentioned systems emphasize the importance of placing the student at the center of their learning by making them a real actor in their development.